Subjective experience of relaxation – induced by vibroacoustic stimulation by a Body Monochord or CD music – a randomised, controlled study in patients with psychosomatic disorders. Issue 1 (1st January 2017) - Sandler, Hubertus; Fendel, Uta; Peters, Eva; Rose, Matthias; Bösel, Rainer; Klapp, Burghard F.
ABSTRACT: Vibroacoustic stimulation via a Body Monochord can induce states of relaxation and subjective well-being. Sometimes unpleasant experiences such as fear, loss of control and unpleasant imagery can occur. Previous results were mainly deduced from investigations in healthy subjects. In this study, we examined psychosomatic patients' subjective experiences during a single treatment with a Body Monochord in comparison to a listening session of relaxation music via audio CD. Diagnosed disorders were anxiety disorders n  = 14, depressive disorders n  = 18, adjustment disorder n  = 27 and somatoform disorders n  = 6. Each of the two treatments took approximately 20 minutes and was presented to the patients in random order. Subjective experiences were recorded via a shortened version of the Phenomenology of Consciousness Inventory. Neither clinical disorders nor psychometric scales for depressiveness and anxiety showed any influence on the emotional experience of the Body Monochord. However, patients with higher depression and anxiety scores showed a tendency to experience the CD music as less emotionally positive. The experience of relaxation induced by the Body Monochord is characterised to a greater extent by release of control (paired t -test: p  = .003, effect size Cohen's d  = .54). Contrary to listening sessions of the CD music, the intensity of imagery during the treatment with the Body Monochord was not related to positive emotional feelings. Possibly during treatment with the Body Monochord psychological defence mechanisms of subjects are more reduced; this may make it easier for unconscious or preconscious contents to appear.